Manajemen Perencanaan dan Penempatan Sumber Daya Manusia Untuk Puskesmas di Kabupaten Indragiri Hilir : Systematic Literature Review - Yoga Saputra; Muhammad Syafa’atul Fitrah. Zm; Meisya Apriyanti; Suci Rabila Siregar; Qayla Meylani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The quality of service at community health centers is still often complained about by the public. Several studies show that the quality of health services at community health centers is closely related to the availability of quality health workers. The aim of the research is to determine various health human resource problems that arise in community health centers which can affect the quality of community health center services, and efforts to overcome various problems related to Human Resources management so that the quality of services at community health centers can be improved. The approach used is a descriptive analysis method. Data obtained from various literature is processed and analyzed qualitatively according to the problems and objectives that have been set. The results obtained show that there are Human Resource problems at the community health center which affect the quality of service, namely the lack of integration of the planning system and procedures for the distribution of health workers; lack of capacity of Human Resources planning units at all levels in the distribution of health workers; lack of good communication so that there are differences in understanding, information and knowledge about the distribution of health workers between planning units and health service providers; lack of support from regional government, planning that is not integrated at various levels of administration in regional government as well as lack of implementation and budgeting of training for health workers at community health centers